International Nursing Actions to Reduce Health Inequities Faced by People with Intellectual and Developmental Disability - Horan, Paul (My University, 2024)
The impact of the COVID-19 pandemic highlighted health inequities for people with intellectual and developmental disability (PWIDD). It was also the stimulus for an international group of nurse researchers with shared expertise and experience to create a Global IDD Nursing Collaboratory. A collaboratory is a networked environment or “center without walls” where interaction oriented to common research areas occur without regard to physical location. The overarching goal of this Global Nursing Collaboratory is to assure the highest quality of life for PWIDD across the lifespan. Applying their unique skills and expertise, nurses working across health and social contexts are often the bridge over the healthcare gaps encountered by PWIDD. This paper describes the potential practice, education, and research contributions nurses can make to reduce health inequities experienced by PWIDD. We will examine how we talk about disability, the impact of the current COVID 19 crisis, and our educational systems which in some countries leave nurses and other health professionals ill prepared to meet the unique needs of this population We will describe the context, access issues, and health service organizations for and with PWIDD across countries to equip nurses with basic knowledge of health care for PWIDD and energize meaningful improvement in delivery of this care. Importantly, we offer action steps for all nurses toward reducing stigma and health inequities related to living with an intellectual and developmental disability (IDD)
PUBLISHED
Keywords: Intellectual Disability, Developmental Disability, Learning Disability; International Development; International Integration; INTELLECTUAL DISABILITIES; NURSING EDUCATION; Intellectual Disability; Globalization